Perceptions and Influential Factors of Beef Consumers During Foot and Mouth Disease in West Sulawesi Province - Pratiwi, Nita Adillah; Ermanda, Adli Putra (Jurnal Peternakan, 2024)
ABSTRACT.  This study aims to determine the response of customer perceptions and factors that influence consumer decisions to buy and consume beef during the foot and mouth disease epidemic that affected cattle in 2022. The variables used in this study consist of several aspects that are thought to influence consumer perceptions, such as product aspects, nutrition and health aspects, knowledge aspects, and product handling aspects, as well as sociodemographic conditions of housewife such as education level, employment status, and location of the area of household, which are used as variables to determine consumer determinants, and 100 housewife data was collected as a sample for this research. The study's findings revealed a significant relationship between housewife education and consumers' perceptions of meat consumption during the FMD pandemics, but no significant correlation between housewife occupations (P>0.005) or household location (P>0.005). During FMD pandemics, housewife education has the most influential factor (P<0.005) on consumer perceptions of beef consumption.